The Effects of Gamification on E-learning Education: Systematic Literature Review and Conceptual Model - Sabri, Zineb; FAKHRI, Youssef; MOUMEN, Aniss (Statistics, Optimization & Information Computing, 2022)
The concept of implementing games or gamifification in education is becoming a growing area in the last decade and a blistering topic among researchers, professors and educational systems. Gaming in education aims to simplify and improve the learning process using technology. Nevertheless, accessibility and inclusion of gaming elements in the higher educational systems inside universities are considered yet. Most of the graduated students endure achieving the mandatory eLearning training to succeed in their integration inside companies. For example, engineers must follow some eLearning courses about Security, Ethics, Agility, Phishing Detection, General Data Protection Regulation...etc., which is tedious. Hence, our research seeks to ease and succeed the integration into companies by applying gamifification to these eLearning courses to engage and motivate students to master them before graduation. This paper discusses the use of games in education, then presents a literature review about learning theories, game theory and design, game development process and tools. By collecting hundreds of papers from multiple research databases, we conceived a journal classifification, a word frequency analysis using cloud visualization. Then a comparative study based on the topic’s occurrences in our corpus. Finally, a comparison of different conceptual models for gamifification of e-learning environments. These results offer an insightful introduction to the application of game elements in educational settings and the implementation of gamifification in e-learning courses.